High-temperature-resistant and corrosion-resistant inorganic phosphate coating applied to steel frame bridge

By developing high-temperature and corrosion-resistant inorganic phosphate coatings, a dense electric double layer coating is formed by using aqueous aluminum dihydrogen phosphate solution, zinc oxide and magnesium oxide, magnesium chromate, tetrabutyl titanate and nano-scale aluminum powder, which solves the problems of high cost, easy aging and complex process flow of traditional corrosion-resistant methods on steel bridges, and achieves efficient corrosion and high-temperature resistance.

CN119662052APending Publication Date: 2025-03-21JIANGSU ZHONGYE TRAFFIC ENG GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601635.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The application of traditional anti-corrosion methods on steel bridges has problems such as high cost, easy aging and complex process flow, making it difficult to effectively prevent steel corrosion.

Method used

A high-temperature and corrosion-resistant inorganic phosphate coating was developed. By using aqueous aluminum dihydrogen phosphate as the binder, zinc oxide and magnesium oxide as the curing agent, magnesium chromate as the passivating agent, tetrabutyl titanate as the auxiliary agent, and nanoscale aluminum powder and modified nanofiller were added to form a dense electric double layer coating to prevent corrosion.

Benefits of technology

It improves the corrosion resistance and high temperature resistance of the coating, effectively blocks the corrosion of external corrosion media on steel, and extends the service life of the steel bridge.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant and corrosion-resistant inorganic phosphate coating applied to a steel frame bridge, and relates to the technical field of corrosion-resistant materials. The preparation method comprises the following steps: placing an aluminum dihydrogen phosphate aqueous solution in a reaction kettle, then adding a curing agent, continuously stirring to completely dissolve the curing agent in the mixed solution, then standing for 1-2 hours to settle part of undissolved impurities, taking supernatant liquid in a beaker, adding a coating passivator, then dropwise adding tetrabutyl titanate while stirring, and standing for 1-2 hours; and adding the functional filler and the modified nano filler after complete dissolution, magnetically stirring for 2 hours to finish the preparation of the coating, standing for 36-48 hours, uniformly stirring again under the condition of ultrasonic oscillation, and then using the coating for air spraying. The product prepared by the invention has excellent corrosion resistance and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion materials, and in particular to a high-temperature resistant and anti-corrosion inorganic phosphate coating applied to steel frame bridges. Background Art

[0002] Steel frame bridges are mainly made of steel and are one of the main types of modern building structures. The annual global steel production exceeds 100 million tons, and the steel equipment scrapped due to corrosion is equivalent to about 30% of the annual production. How to improve the rust removal and anti-corrosion construction process of steel frame bridges has become an urgent problem to be solved. Steel frame bridges are exposed to the wild environment, and their surfaces are easily corroded by chemical and electrochemical reactions with the surrounding environment. Therefore, it is necessary to carry out anti-corrosion treatment on their surface to protect the steel frame bridge body from rust. Steel frame bridge buildings are generally large permanent buildings with long service life and difficult maintenance. Effective long-term anti-corrosion must be carried out to ensure the service life of the building.

[0003] In order to reduce the economic losses caused by metal corrosion, it is of great significance to protect metal resources. On the one hand, reducing metal corrosion can strengthen environmental protection; on the other hand, it is very important to enhance resource availability and reduce economic losses. It is necessary to take effective protective measures against metal waste, but traditional anti-corrosion methods have certain disadvantages, such as high cost, easy aging, and complicated process flow when applied to steel.

[0004] As part of coating preparation science, there is still a lot of room for the development of coatings. Under the advocacy of environmentally friendly chemistry, inorganic coatings and their derivatives will also develop rapidly. Phosphate coatings are a new type of inorganic coatings in recent years, but there are still many unknown problems in their preparation science and application process. Therefore, improving the preparation science, adhesion theory, coating removal and aging of phosphate system coatings and improving their applicability will be the focus of the future development of phosphate coatings. Therefore, it is urgent to develop a high temperature resistant and corrosion resistant inorganic phosphate coating for use on steel frame bridges. Summary of the invention

[0005] The purpose of the present invention is to provide a high temperature resistant and corrosion resistant inorganic phosphate coating for use on steel frame bridges to solve the problems raised in the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A high temperature resistant and corrosion resistant inorganic phosphate coating used on steel frame bridges is composed of the following raw materials in parts by weight: 40-50 parts of phosphate binder, 1-2 parts of curing agent, 0.5-0.8 parts of coating passivator, 3-5 parts of functional filler, 3-5 parts of modified nano filler and 3-5 parts of tetrabutyl titanate.

[0008] Preferably, the phosphate binder is an aqueous solution of aluminum dihydrogen phosphate with a mass fraction of 30-35%.

[0009] Preferably, the curing agent is prepared by mixing zinc oxide and magnesium oxide in a mass ratio of 1:3-1:5.

[0010] Preferably, the coating passivating agent is magnesium chromate.

[0011] Preferably, the functional filler is prepared by mixing nano-scale aluminum powder and micron-sized spherical aluminum powder in a mass ratio of 1:2-1:3.

[0012] Preferably, the preparation method of the modified nanofiller is:

[0013] According to weight, 5-8 parts of magnesium chloride hexahydrate, 5-8 parts of aluminum chloride hexahydrate, 4-6 parts of sodium hydroxide, 50-80 parts of deionized water A, 50-80 parts of deionized water B, 2-3 parts of sodium carbonate and 2-3 parts of formamide are taken, and the magnesium chloride hexahydrate, aluminum chloride hexahydrate and deionized water A are placed in a reactor 1, and stirred evenly with a magnetic stirrer at a speed of 800-1000r / min for standby use, sodium hydroxide is dissolved in deionized water B and then placed in a reactor 2 for uniform dispersion, and then sodium carbonate and formamide are placed in a reactor 3, and after heating to 80-85°C, the liquids in the reactors 1 and 2 are added to the reactor 3 at a speed of 1.2-1.6mL / min using a peristaltic pump at a speed of 800-1000r / min. After the reaction is completed, the generated liquid is poured into a centrifuge and washed with deionized water for 3-5 times to obtain a modified nanofiller.

[0014] Preferably, the coating is prepared by:

[0015] Place the aluminum dihydrogen phosphate aqueous solution in a reactor, then add the curing agent, stir continuously to make the curing agent completely dissolved in the mixed solution, then let it stand for 1-2 hours to allow some undissolved impurities to settle, take the upper clear liquid in a beaker and add the coating passivator, then add tetrabutyl titanate dropwise while stirring, add functional fillers and modified nanofillers after complete dissolution, and prepare the coating after magnetic stirring for 2 hours. Let it stand for 36-48 hours, then re-stir under ultrasonic vibration to make it uniform, and then it can be used for air spraying.

[0016] As a preferred method, the use method of the high temperature resistant and corrosion resistant inorganic phosphate coating is:

[0017] The preparation of the coating is divided into two main steps: coating and film curing. The alloy sample is surface coated by room temperature air spraying. Two coats of coating are used. The second coat is applied after the first coat is dry. The coating is then prepared by a step-by-step drying method at 30-130°C for 1 hour in a constant temperature oven.

[0018] In summary, due to the adoption of the above technology, the beneficial effects of the present invention are:

[0019] The present invention uses aluminum dihydrogen phosphate aqueous solution as a coating phosphate binder, zinc oxide and magnesium oxide as aluminum dihydrogen phosphate curing agents, and magnesium chromate as a coating passivator to inhibit the reaction between aluminum powder filler and acidic coating. Tetrabutyl titanate is used as an auxiliary agent in the topcoat coating. The nano-grade aluminum powder and micron spherical aluminum powder used in the topcoat can provide a dense coating surface, effectively hinder the corrosion of the external corrosive medium on the steel surface, and improve the anti-corrosion performance and high temperature resistance of the product.

[0020] The modified nano filler added in the product of the present invention, wherein the anions in the delaminated hydrotalcite and the chloride ions in the corrosive medium repel each other, has excellent corrosion resistance compared to ordinary inorganic phosphate coatings. When the anions penetrate from the corrosive medium into the coating, the mutual repulsion is enhanced, which plays a certain protective role on the coating, and the corrosive ions are not easy to enter the interior of the coating. The double-layer coating protects the steel structure, thereby improving the corrosion resistance and high temperature resistance of the product. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0022] Example 1

[0023] A high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge is composed of the following raw materials in parts by weight: 40 parts of a phosphate binder, 2 parts of a curing agent, 0.5 parts of a coating passivator, 5 parts of a functional filler, 5 parts of a modified nano filler, and 5 parts of tetrabutyl titanate.

[0024] The phosphate binder is an aqueous solution of aluminum dihydrogen phosphate with a mass fraction of 30%.

[0025] The curing agent is prepared by mixing zinc oxide and magnesium oxide in a mass ratio of 1:5.

[0026] The paint passivator is magnesium chromate.

[0027] The functional filler is prepared by mixing nano-grade aluminum powder and micron-sized spherical aluminum powder in a mass ratio of 1:2.

[0028] The preparation method of the modified nanofiller is:

[0029] By weight, 8 parts of magnesium chloride hexahydrate, 5 parts of aluminum chloride hexahydrate, 6 parts of sodium hydroxide, 50 parts of deionized water A, 80 parts of deionized water B, 2 parts of sodium carbonate and 3 parts of formamide are taken, and the magnesium chloride hexahydrate, aluminum chloride hexahydrate and deionized water A are placed in a reactor 1, and stirred evenly with a magnetic stirrer at a speed of 1000 r / min for standby use, sodium hydroxide is dissolved in deionized water B and placed in a reactor 2 for uniform dispersion, and then sodium carbonate and formamide are placed in a reactor 3, and after heating to 85° C., the liquids in reactors 1 and 2 are added to the reactor 3 at a speed of 1.2 mL / min using a peristaltic pump at a speed of 1000 r / min. After the reaction is completed, the generated liquid is poured into a centrifuge and washed 5 times with deionized water to obtain a modified nanofiller.

[0030] The preparation process of the coating is:

[0031] Place the aluminum dihydrogen phosphate aqueous solution in a reactor, then add the curing agent, stir continuously to allow the curing agent to completely dissolve in the mixed solution, then let it stand for 2 hours to allow some undissolved impurities to settle, take the upper clear liquid in a beaker and add the coating passivator, then add tetrabutyl titanate dropwise while stirring, add functional fillers and modified nanofillers after complete dissolution, and prepare the coating after magnetic stirring for 2 hours. Let it stand for 36 hours, then re-stir under ultrasonic vibration to make it uniform, and then it can be used for air spraying.

[0032] The use method of high temperature resistant and corrosion resistant inorganic phosphate coating is:

[0033] The preparation of the coating is divided into two main steps: coating and film curing. The alloy sample is surface coated by air spraying at room temperature. Two coats of coating are used. The second coat is applied after the first coat is dry. The coating is then prepared by step-by-step drying at 30°C for 1 hour in a constant temperature oven.

[0034] Example 2

[0035] A high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge is composed of the following raw materials in parts by weight: 50 parts of a phosphate binder, 2 parts of a curing agent, 0.8 parts of a coating passivator, 5 parts of a functional filler, 5 parts of a modified nano filler, and 5 parts of tetrabutyl titanate.

[0036] The phosphate binder is an aqueous solution of aluminum dihydrogen phosphate with a mass fraction of 30%.

[0037] The curing agent is prepared by mixing zinc oxide and magnesium oxide in a mass ratio of 1:5.

[0038] The paint passivator is magnesium chromate.

[0039] The functional filler is prepared by mixing nano-grade aluminum powder and micron-sized spherical aluminum powder in a mass ratio of 1:2.

[0040] The preparation method of the modified nanofiller is:

[0041] By weight, 8 parts of magnesium chloride hexahydrate, 5 parts of aluminum chloride hexahydrate, 5 parts of sodium hydroxide, 80 parts of deionized water A, 80 parts of deionized water B, 2 parts of sodium carbonate and 3 parts of formamide are taken, and the magnesium chloride hexahydrate, aluminum chloride hexahydrate and deionized water A are placed in a reactor 1, and stirred evenly with a magnetic stirrer at a speed of 800 r / min for standby use, sodium hydroxide is dissolved in deionized water B and placed in a reactor 2 for uniform dispersion, and then sodium carbonate and formamide are placed in a reactor 3, and after heating to 85° C., the liquids in reactors 1 and 2 are added to the reactor 3 at a speed of 800 r / min using a peristaltic pump at a rate of 1.6 mL / min. After the reaction is completed, the generated liquid is poured into a centrifuge and washed 5 times with deionized water to obtain a modified nanofiller.

[0042] The preparation process of the coating is:

[0043] Place the aluminum dihydrogen phosphate aqueous solution in a reactor, then add the curing agent, stir continuously to allow the curing agent to completely dissolve in the mixed solution, then let it stand for 2 hours to allow some undissolved impurities to settle, take the upper clear liquid in a beaker and add the coating passivator, then add tetrabutyl titanate dropwise while stirring, add functional fillers and modified nanofillers after complete dissolution, and prepare the coating after magnetic stirring for 2 hours. Let it stand for 36 hours, then re-stir under ultrasonic vibration to make it uniform, and then it can be used for air spraying.

[0044] The use method of high temperature resistant and corrosion resistant inorganic phosphate coating is:

[0045] The preparation of the coating is divided into two main steps: coating and film curing. The alloy sample is surface coated by air spraying at room temperature. Two coats of coating are used. The second coat is applied after the first coat is dry. The coating is then prepared by step-by-step drying at 130°C for 1 hour in a constant temperature oven.

[0046] Example 3

[0047] A high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge is composed of the following raw materials in parts by weight: 50 parts of a phosphate binder, 2 parts of a curing agent, 0.7 parts of a coating passivator, 3 parts of a functional filler, 5 parts of a modified nano filler, and 5 parts of tetrabutyl titanate.

[0048] The phosphate binder is an aqueous solution of aluminum dihydrogen phosphate with a mass fraction of 30%.

[0049] The curing agent is prepared by mixing zinc oxide and magnesium oxide in a mass ratio of 1:5.

[0050] The paint passivator is magnesium chromate.

[0051] The functional filler is prepared by mixing nano-grade aluminum powder and micron-sized spherical aluminum powder in a mass ratio of 1:3.

[0052] The preparation method of the modified nanofiller is:

[0053] By weight, 5 parts of magnesium chloride hexahydrate, 8 parts of aluminum chloride hexahydrate, 6 parts of sodium hydroxide, 50 parts of deionized water A, 80 parts of deionized water B, 3 parts of sodium carbonate and 3 parts of formamide are taken, and the magnesium chloride hexahydrate, aluminum chloride hexahydrate and deionized water A are placed in a reactor 1, and stirred evenly with a magnetic stirrer at a speed of 800 r / min for standby use, sodium hydroxide is dissolved in deionized water B and placed in a reactor 2 for uniform dispersion, and then sodium carbonate and formamide are placed in a reactor 3, and after heating to 85° C., the liquids in reactors 1 and 2 are added to the reactor 3 at a speed of 1000 r / min using a peristaltic pump at 1.2 mL / min. After the reaction is completed, the generated liquid is poured into a centrifuge and washed 5 times with deionized water to obtain a modified nanofiller.

[0054] The preparation process of the coating is:

[0055] Place the aluminum dihydrogen phosphate aqueous solution in a reactor, then add the curing agent, stir continuously to make the curing agent completely dissolved in the mixed solution, then let it stand for 1 hour to allow some undissolved impurities to settle, take the upper clear liquid in a beaker and add the coating passivator, then add tetrabutyl titanate dropwise while stirring, add functional fillers and modified nanofillers after complete dissolution, and prepare the coating after magnetic stirring for 2 hours. Let it stand for 48 hours, then re-stir under ultrasonic vibration to make it uniform, and then it can be used for air spraying.

[0056] The use method of high temperature resistant and corrosion resistant inorganic phosphate coating is:

[0057] The preparation of the coating is divided into two main steps: coating and film curing. The alloy sample is surface coated by air spraying at room temperature. Two coats of coating are used. The second coat is applied after the first coat is dry. The coating is then prepared by step-by-step drying at 30°C for 1 hour in a constant temperature oven.

[0058] Detection:

[0059] The specific index system of the coating is as follows:

[0060] 1) Conventional performance: 24h room temperature curing or 4h high temperature curing can be achieved; Adhesion ≥15MPa (GB / T 5210); Flexibility 1mm (GB / T 1731); Impact strength >50KJ cm-2 (GB / T 1732).

[0061] 2) Thermal shock resistance: 700℃ thermal shock resistance water quenching test> 100 times, the coating is intact without blistering, peeling and flaking.

[0062] 3) High temperature oxidation resistance: 650℃ grade oxidation ≥10000h, with complete oxidation resistance.

[0063] 4) High temperature water vapor corrosion resistance: 650℃, 25Mpa water vapor environment ≥1000h, with complete anti-oxidation performance

[0064] 5) At the same time, conduct 650℃, 25Mpa water vapor comparative oxidation test for ≥1000 hours for materials and coatings used in 650℃ ultra-supercritical units;

[0065] 6) Toxicity: in line with GJB 11B-2012, storage stability: >6 months, mildew resistance: greater than 1000h.

[0066] After testing, Examples 1-3 all meet the above indicators. The present invention uses aluminum dihydrogen phosphate aqueous solution as a coating phosphate binder, zinc oxide and magnesium oxide as aluminum dihydrogen phosphate curing agents, and magnesium chromate as a coating passivator to inhibit the reaction between aluminum powder filler and acidic coating. Tetrabutyl titanate is used as an auxiliary agent in the topcoat coating. The nano-scale aluminum powder and micron spherical aluminum powder used in the topcoat can provide a dense coating surface, effectively hinder the erosion of the external corrosive medium on the steel surface, and improve the product's anti-corrosion performance and high temperature resistance.

[0067] The modified nano filler added in the product of the present invention, wherein the anions in the delaminated hydrotalcite and the chloride ions in the corrosive medium repel each other, has excellent corrosion resistance compared to ordinary inorganic phosphate coatings. When the anions penetrate from the corrosive medium into the coating, the mutual repulsion is enhanced, which plays a certain protective role on the coating, and the corrosive ions are not easy to enter the interior of the coating. The double-layer coating protects the steel structure, thereby improving the corrosion resistance and high temperature resistance of the product.

[0068] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

Claims

1. A high temperature resistant and corrosion resistant inorganic phosphate coating applied to a steel frame bridge, characterized in that: The invention is composed of the following raw materials in parts by weight: 40-50 parts of phosphate binder, 1-2 parts of curing agent, 0.5-0.8 parts of coating passivator, 3-5 parts of functional filler, 3-5 parts of modified nano filler and 3-5 parts of tetrabutyl titanate.

2. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 1, characterized in that: The phosphate binder is an aqueous solution of aluminum dihydrogen phosphate with a mass fraction of 30-35%.

3. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 2, characterized in that: The curing agent is prepared by mixing zinc oxide and magnesium oxide in a mass ratio of 1:3-1:

5.

4. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 3, characterized in that: The coating passivating agent is magnesium chromate.

5. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 4, characterized in that: The functional filler is prepared by mixing nano-grade aluminum powder and micron-sized spherical aluminum powder in a mass ratio of 1:2-1:

3.

6. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 5, characterized in that: The preparation method of the modified nanofiller is: According to weight, 5-8 parts of magnesium chloride hexahydrate, 5-8 parts of aluminum chloride hexahydrate, 4-6 parts of sodium hydroxide, 50-80 parts of deionized water A, 50-80 parts of deionized water B, 2-3 parts of sodium carbonate and 2-3 parts of formamide are taken, and the magnesium chloride hexahydrate, aluminum chloride hexahydrate and deionized water A are placed in a reactor 1, and stirred evenly with a magnetic stirrer at a speed of 800-1000r / min for standby use, sodium hydroxide is dissolved in deionized water B and then placed in a reactor 2 for uniform dispersion, and then sodium carbonate and formamide are placed in a reactor 3, and after heating to 80-85°C, the liquids in the reactors 1 and 2 are added to the reactor 3 at a speed of 1.2-1.6mL / min using a peristaltic pump at a speed of 800-1000r / min. After the reaction is completed, the generated liquid is poured into a centrifuge and washed with deionized water for 3-5 times to obtain a modified nanofiller.

7. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 6, characterized in that: The preparation process of the coating is: Place the aluminum dihydrogen phosphate aqueous solution in a reactor, then add the curing agent, stir continuously to make the curing agent completely dissolved in the mixed solution, then let it stand for 1-2 hours to allow some undissolved impurities to settle, take the upper clear liquid in a beaker and add the coating passivator, then add tetrabutyl titanate dropwise while stirring, add functional fillers and modified nanofillers after complete dissolution, and prepare the coating after magnetic stirring for 2 hours. Let it stand for 36-48 hours, then re-stir under ultrasonic vibration to make it uniform, and then it can be used for air spraying.

8. The high temperature resistant and corrosion resistant inorganic phosphate coating used on a steel frame bridge according to claim 7, characterized in that: The method for using the high temperature resistant and corrosion resistant inorganic phosphate coating is as follows: The preparation of the coating is divided into two main steps: coating and film curing. The alloy sample is surface coated by room temperature air spraying. Two coats of coating are used. The second coat is applied after the first coat is dry. The coating is then prepared by a step-by-step drying method at 30-130°C for 1 hour in a constant temperature oven.